Do we need 30 min cortisol measurement in the short synacthen test: a retrospective study. Issue 1138 (6th December 2019) - Kumar, Rajeev; Carr, Peter; Moore, Kimberley; Rajput, Zeeshan; Ward, Louise; Wassif, W S
Abstract: Objective: The short synacthen test (SST) is widely used across the UK to assess adrenal reserve but there remains no consensus on the timing of cortisol sampling to help diagnose adrenal insufficiency. The main objective of our study was to see if both 30 and 60 min sample are required following administration of synacthen to investigate suspected adrenal insufficiency (AI). Design: This was a single-centre retrospective study of 393 SSTs measuring 0, 30 and 60 min cortisol levels after administration of 250 µg of synacthen. Patients and methods: All the SSTs for patients suspected of primary or secondary AI between April 2016 and October 2018 were included in this study. The tests were performed as per our hospital protocol. A post-adrenocorticotropic hormone (ACTH) cortisol response of 420 nmol/L at any time point was considered adequate to rule out AI. The data were analysed to ascertain the proportion of patients who achieved this level at 30 and/or 60 min. Results: A total of 393 SST results were included in this study. Patients were divided into two groups depending on whether (group A) or not (group B) they were on steroids. Overall, a total of 313 (79.6%) subjects achieved cortisol level of ≥420 nmol/L at 30 and 60 min while 19 (4.8%) had late response (ie, insufficient 30 min cortisol levels, rising to ≥420 nmol/L at 60 min). Another 61 subjects (15.5%) showed insufficient response at both 30 and 60 min (ie, failed to achieved level of ≥420 nmol/L). Importantly, there was no patient in either group who had adequate response at 30 min and then failed at 60 min. Patients in group A were more likely to have inadequate response at both 30 and 60 min while patients in group B were more likely to have normal response at both time points. Conclusions: Our results suggest that about 5% of people undergoing SST may be inappropriately diagnosed as having AI (and subjected to long-term unnecessary steroid treatment) if the 60 min sample is not maintained. We suggest that 30 min sample does not add any additional diagnostic utility and can be omitted thus simplifying SST even further and saving on cost and resources. We propose that single measurement after 60 min of administration of synthetic ACTH is a sufficient screening test for AI.